Russia and Germany : A New Future? - Cheang, Chris (2019)
Russia’s Eurocentric foreign policy is focused on Germany, its most significant partner in Europe. The Trump administration’s policies towards Germany, and the rise of anti-EU and anti-NATO populist parties in Europe and Germany itself, could undo the status quo − Germany could seek a closer relationship with Russia.